Conceptualizing multicultural discourses of security: introduction to the special issue*. Issue 4 (2nd October 2017) - Taylor, Bryan C.; Bean, Hamilton
ABSTRACT: This introduction to the special issue reviews recent developments in interdisciplinary scholarship on security, discourse, and culture. It then reviews recent work in fields of critical intercultural studies to associate these developments with the commitments of Cultural Discourse Studies. It concludes by previewing the essays collected for this issue.